Unravelling the potential of effective seed bacterial endophyte in groundnut for stem rot disease (Sclerotium rolfsii) management: Unravelling the potential of effective seed bacterial endophyte in groundnut for stem rot disease (Sclerotium rolfsii) management - T ARCHANA; L RAJENDRAN; S K MANORANJITHAM; V P SANTHANA KRISHNAN; G KARTHIKEYAN (Journal of Oilseeds Research, 2023)
Groundnut (Arachis hypogaea L.) is known as “King of oilseeds” which is grown extensively in both Kharif and Rabi/Summer seasons.Several among the several pathogens, Stem rot caused by Sclerotium rolfsii Sacc. causes the yield loss up to 80 per cent during favourable conditions. Hence, an attempt has been made to isolate bacterial endophytes for biocontrol management from peanut seeds as an alternative approach. Sixteen isolates (EGN1- EGN16) isolated from peanut were tested against Sclerotium rolfsii under in vitro. Further, the effective isolates were further analyzed for the presence of thermo stable compounds, profiling of secondary metabolites through GC-MS analysis, growth promotion test (rhizo scanner) and pot culture experiment. The results showed that talc formulation of effective isolate EGN 1 (Pseudomonas sp.) significantly increased the vigour index (4902.81), germination rate (91.3per cent), root length (28.1 cm) and shoot length (25.6 cm) along with the simultaneous reduction in disease incidence of 5.54 %.